2021
DOI: 10.21037/jgo-21-821
|View full text |Cite
|
Sign up to set email alerts
|

A three-phase trans-ethnic study reveals B7-H3 expression is a significant and independent biomarker associated with colon cancer overall survival

Abstract: Background: There have been inconsistent results and conflicting conclusions among the existing prognostic studies of B7-H3 expression in colon cancer patients. Therefore, the association between B7-H3 expression and colon cancer survival has remained largely unclear.Methods: We performed a three-phase and trans-ethnic prognostic study of B7-H3 expression in colon cancer patients involving perhaps the largest population to date. In the discovery phase, we utilized a Cox proportional hazards model adjusted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Some other studies found that B7-H3, B7-H4 and B7-H7 expression in colorectal cancer was significantly upregulated as compared with normal tissues. The high expression of these molecules was correlated with a poor outcome in patients with colorectal cancer [ 109 , 110 , 111 , 112 ]. In 2020, Yasui et al published a study whose aim was to investigate the effect of chemoradiotherapy on the immunological status of rectal cancer patients who were treated with preoperative chemoradiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Some other studies found that B7-H3, B7-H4 and B7-H7 expression in colorectal cancer was significantly upregulated as compared with normal tissues. The high expression of these molecules was correlated with a poor outcome in patients with colorectal cancer [ 109 , 110 , 111 , 112 ]. In 2020, Yasui et al published a study whose aim was to investigate the effect of chemoradiotherapy on the immunological status of rectal cancer patients who were treated with preoperative chemoradiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…B7-H3 is a vital factor in CRC which not only functions as a marker of CRC prognosis and clinicopathological stage ( 9 - 11 ), but also promotes CRC in many ways ( 7 , 8 , 12 ). In CRC, B7-H3 serves as a significant biomarker for survival ( 10 ). As an immune checkpoint protein, B7-H3 can inhibit the function of anti-tumor immune cells in many ways ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a transmembrane protein, B7-H3 is expressed in the pro-B7-H3 form on the membrane of various tumors, and further cleaved by matrix metalloproteinase (MMP) to yield soluble B7-H3 that performs cellular functions ( 6 ). In CRC, B7-H3 promotes the tumor progression ( 7 , 8 ) and is associated with recurrence and overall survival ( 9 , 10 ). Highly B7-H3 expression is associated with enhanced lymph node metastasis and poor tumor differentiation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the correlation between the expression values of prognosis-related proteins involved in the construction of prognostic models and various clinical phenotypes (including patient age, gender, stage, etc. ), calculated the correlation coe cients and P-values between them, and drew correlation boxplots to visualize the results with statistical differences 29,30 .…”
Section: Analysis Of Correlation Between Prognosis-related Proteins A...mentioning
confidence: 99%